2020
DOI: 10.1007/s11368-020-02600-8
|View full text |Cite
|
Sign up to set email alerts
|

Sediment load variability in response to climate and land use changes in a Carpathian catchment (Raba River, Poland)

Abstract: Purpose This study analyzes the variability of sediment loads under variant climate change and land use scenarios in a Carpathian catchment with a dam reservoir. The areas with the highest share of sediment loads are tracked to establish possible indications for future catchment management plans. Materials and methods Analyses were performed for the Raba River catchment (Poland, Carpathian Mountains) with use of the Macromodel DNS/SWAT. The RCP 4.5 climate forecast predictions (2021-2050 and 2071-2100), downsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…To achieve the goal of the study, i.e., to track sediment particles from their source to the deposition area, the DNS (Discharge Nutrient Sea) digital platform (Macromodel DNS) has been used as a modeling tool. The Macromodel DNS, developed at the Institute of Meteorology and Water Management-National Research Institute (Instytut Meteorologii i Gospodarki Wodnej-Państwowy Instytut Badawczy, IMGW-PIB) (Wilk et al 2018b;Wilk and Orlińska-Woźniak 2019), provides an interactive platform allowing for integration of the SWAT (Soil and Water Assessment Tool) module (version 2012) (Arnold et al 2012;Abbaspour et al 2015) with other modeling tools (modules) to track different processes of the sediment/contaminant transport in a catchment (Wilk et al 2018a;Szalińska et al 2020Szalińska et al , 2021Orlińska-Woźniak et al 2020a). The RR catchment module has been created in the SWAT module (Fig.…”
Section: Modeling Toolmentioning
confidence: 99%
See 2 more Smart Citations
“…To achieve the goal of the study, i.e., to track sediment particles from their source to the deposition area, the DNS (Discharge Nutrient Sea) digital platform (Macromodel DNS) has been used as a modeling tool. The Macromodel DNS, developed at the Institute of Meteorology and Water Management-National Research Institute (Instytut Meteorologii i Gospodarki Wodnej-Państwowy Instytut Badawczy, IMGW-PIB) (Wilk et al 2018b;Wilk and Orlińska-Woźniak 2019), provides an interactive platform allowing for integration of the SWAT (Soil and Water Assessment Tool) module (version 2012) (Arnold et al 2012;Abbaspour et al 2015) with other modeling tools (modules) to track different processes of the sediment/contaminant transport in a catchment (Wilk et al 2018a;Szalińska et al 2020Szalińska et al , 2021Orlińska-Woźniak et al 2020a). The RR catchment module has been created in the SWAT module (Fig.…”
Section: Modeling Toolmentioning
confidence: 99%
“…Already, many mountain catchments are struggling with an increase in soil loss due to intensification of rainfall, and consequently, surface runoff (Halecki et al 2018a, b;Borrelli et al 2018;Mostowik et al 2019;Berteni and Grossi 2020;Ciampalini et al 2020). Moreover, the forecasted changes in precipitation and temperature suggest that the intensity of this phenomenon may increase significantly (Borrelli et al 2020;Gianinetto et al 2020;Szalińska et al 2020). It also turns out that in such areas, even favorable changes in land use (LU) associated with a significant increase in the area of forests, which naturally stabilize the soil, may turn out to be insufficient to stop the negative effects of the climate changes (Orlińska-Woźniak et al 2020a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scheduled operation rule curve of a reservoir to augment its water for irrigation, hydropower, flood control, navigation or recreation has become controversial in various conflicting issues like space, time and discharge. As a result, majority of old, reservoirs have turned geriatric and warrant to be modified in view of sediment administration for its sustainability based on catchment characteristics, [2,11,12,13]. Rengali Reservoir over river Brahmani in Odisha is one such example (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…A par tic u larly im por tant role is played by human ac tiv ity, more spe cif i cally, the type of land use (for estry, ag ri cul tural, in dus trial, res i den tial) and the mod i fi ca tions to the catch ment land scape (hydrotechnical con struc tions, res ervoirs, mines, the trans port net work con struc tion and road-surface ero sion). Re search has found that an in crease in the amount of trans ported sus pended par ti cles is gen er ally in fluenced by fac tors lead ing to soil ero sion in the catch ment area, such as cli mate and the type of land cover (e.g., Wall ing and Webb, 1996;Sinha et al, 2020;Szaliñska et al, 2020). A close look at this ques tion shows that de spite de cades of re search, the pre cise fac tors in flu enc ing how sed i ment flux var ies in rivers, and which in ter con nec tions are sig nif i cant, re main unclear (Vercruysse et al, 2017;Peng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%